Biomarkers in rock oysters (Saccostrea mordax) in response to organophosphate pesticides - Kennedy Opiyo; Christopher Rawson; Marthe Monique Gagnon; Ishaaq Saputra (Marine Science Department Diponegoro University, 2021)
Chlorpyrifos is a xenobiotics contaminants that threats the marine environment and the living organism within the habitat. Although several marine bivalve species have been used as the indicator of marine pollution, the used of Saccostrea mordax is remaining unknown. This study aimed at investigating the suitability of lysosome membrane integrity, carboxylesterase activity, 8-oxo-2′-deoxyguanosine and condition index as biomarkers in adult S. mordax following their exposure to 0.0, 5.0 and 500 μg.L-1 of Chlorpyrifos for 21 days under laboratory conditions. Results indicated that the lysosome membrane integrity showed a dose-dependent response with a significant statistical number of destabilized cells between all the treatment groups. Carboxylesterase activity was significantly inhibited in 500 μg.L-1 chlorpyrifos treated group, while the environmentally relevant concentration (5 μg.L-1) did not induce a significant inhibition with reference to the control. Similarly, the condition index showed a dose-dependent response with the oysters exposed to 500 μg.L-1 chlorpyrifos exhibiting a significantly reduced growth rate. There was no statistical significance in the means of both 8-oxo-2′-deoxyguanosine in all treatment groups. The reaction of S. mordax to chlorpyrifos contamination demonstrates that the species can potentially be used as sentinel organisms in environmental monitoring programs. Lysosome membrane integrity was a single out as a sensitive biomarker for exposure to chlorpyrifos and is therefore suitable for environmental monitoring for sublethal concentrations of chlorpyrifos contaminations. Additionally, the use of multiple biomarkers was found to be robust in this study and can be extrapolated to other ecotoxicological studies